Resection of Thumb Metacarpal Ewing Sarcoma and Primary Reconstruction with Non-Vascularized Osteoarticular Metatarsal Autograft - MS, Ariff; WI, Faisham; J, Krishnan; W, Zulmi (IIUM Medical Journal Malaysia, 2015)
Ewing sarcoma is a primary bone malignancy that rarely occurs in the hand. Resection and reconstruction will usually result in reduced or loss of thumb function. We describe a case of successful transplantation of nonvascularized osteoarticular second metatarsal autograft following wide resection of Ewing sarcoma of first metacarpal in an 11-year-old girl. The capsule of the graft’s metatarso-phalangeal joint was repaired to achieve mobility of the joint. This enabled preservation of thumb function by a relatively simple surgical technique. Detailed surgical procedures and excellence function after 2 years following surgery are described.